Aesthetic Symbols of Travesty in Ludruk Karya Budaya - Hidayat, Achmad Fahmi; Triyanto, Triyanto; lestari, Wahyu (Universitas Negeri Semarang, 2021)
The Ludruk Karya Budaya art group is one of the largest groups in East Java. It still maintains the travesty in its performance. A travesty is a form of existence consisting of a set of female roles a man plays. It can be studied in terms of the form, symbol, and role in Ludruk Karya Budaya. The purpose of this study is related to the issues raised, namely revealing the problem, symbols, and the role of travesty in Ludruk Karya Budaya. This study uses a qualitative method. Qualitative research with the research approach used in this study is phenomenology. Data collection techniques used observation techniques, interviews, and document studies. The data validation technique uses source triangulation. Analysis was conducted through data reduction, data presentation, and data verification stages. The results of the study show the following. First, travesty is interpreted as a presentational symbol and a discursive symbol. The researcher analyzed the meaning of presentational and discursive symbols using Suzanne Langer's symbol theory. The researcher interprets the presentational symbol of a travesty in the clothes, makeup, dancing, singing, and stylizing like a woman, and the meaning of the discursive symbol is an abstraction that makes the travesty artist express an expression that can attract the audience's interest by using the appeal of a strange visual form of a travesty artist.